The Effects of Acute and Chronic Sprint-Interval Training on Cytokine Responses Are Independent of Prior Caffeine Intake - Ferreira, Guilherme A.; Felippe, Leandro C.; Bertuzzi, Rômulo; Bishop, David J.; Barreto, Emiliano; De-Oliveira, Fernando R.; Lima-Silva, Adriano E. (Frontiers in Physiology, 2018)
We examined the effect of acute and chronic sprint interval training (SIT), with or without prior caffeine intake, on levels of exercise-induced inflammatory plasma cytokines (interleukin (IL)-6, IL-10, tumor necrosis factor (TNF)-α. Twenty physically-active men ingested either a placebo (n = 10) or caffeine (n = 10) one hour before each SIT session (13 x 30-s sprint/15 s of rest) during six training sessions (2 weeks). The early (before, immediately after, and 45 min after the exercise) and late (24 and 48 h after the exercise) cytokine and creatine kinase (CK) responses were analyzed for the first and last training sessions. Plasma IL-6 and IL-10 peaked 45 min after the exercise, and then returned to basal values within 24 h (p < 0.05) in both groups on both occasions (p > 0.05). On both occasions, and for both groups, plasma TNF-α increased from rest to immediately after the exercise and then decreased at 45 minutes before reaching values at or below basal levels 48 h after the exercise (p < 0.05). Serum CK increased from rest to 24 and 48 h post exercise in the first training session (p < 0.05), but did not alter in the last training session for the PLA group (p > 0.05). Serum CK was unchanged in both the first and last training sessions for the CAF group (p > 0.05). Two weeks of SIT induced a late decrease in the IL-6/IL-10 ratio (p < 0.05) regardless of caffeine intake, suggesting an improved overall inflammatory status after training. In conclusion, a single session of SIT induces muscle damage that seems to be mitigated by caffeine intake. Two weeks of SIT improves the late SIT-induced muscle damage and inflammatory status, which seems to be independent of caffeine intake.